A randomised controlled trial of morphine versus phenobarbitone for neonatal abstinence syndrome. Issue 4 (21st June 2004) - Jackson, L; Ting, A; Mckay, S; Galea, P; Skeoch, C
Abstract : Background: The incidence of neonatal abstinence syndrome (NAS) has increased 10-fold over the last decade in Glasgow. In the Princess Royal Maternity Hospital, it now accounts for 17% of special care baby unit (SCBU) admissions. Objective: To compare opiate replacement therapy (morphine sulphate) with the present standard treatment (phenobarbitone) for management of NAS. The primary study end point was duration of pharmaceutical treatment. Secondary end points were the requirement for additional drugs and the requirement for SCBU admission. Design: Double blind, randomised controlled clinical trial. Methods: Differential diagnoses were excluded, and two consecutive Lipsitz scores > 4 defined NAS requiring treatment. Infants were randomised to receive morphine sulphate or phenobarbitone. Treatments were identical in appearance, odour, and volume. Increments, decrements, and discontinuation of treatments were protocol driven. Results: Seventy five infants participated. All mothers received opiate replacement therapy (methadone) during pregnancy and most used other drugs (n = 62, 83%). No significant difference in maternal drug use patterns was observed between treatment groups. Median treatment duration was four days shorter with opiate replacement (8 v 12 days, Mann-Whitney U test, p = 0.02). Phenobarbitone treated infants tended to require second line treatment (47% v 35%, χ 2 test, p = 0.11) and SCBU admission (62% v 30%, χ 2 test, p = 0.04) more often. Conclusions: Opiate replacement therapy appears to be superior for management of symptomatic NAS when maternal opiate use is prevalent. The shorter treatment duration and lower requirement for higher intensity nursing may have significant cost implications. Tailoring NAS treatment to local maternal drug use may result in similar benefits.